Segmentação de mercados e afrodescendência: uma análise em Salvador - Ba - Santos, Isabela Lacerda (2007)
Stimulated by the growth of the purchasing power of the Afro-descendant population in Brazil, the market hás been increasingly getting ready for that group of consumers. The figures relative to the Afro-Brazilian population would by themselves justify the relevance of studies that could show enterprises the patterns of consumption of that slice of the population. Even so the racial issue does not seem to have reached the marketing field with the same strength with which it reached the social and economic field the market segmentation to fit racial characteristics is still an incipient activity in Brazil, even with half the country s population being composed of Afro-descendants. Within the current parameters, 12% of the population in the capital of Bahia have an above-ten-minimum-wage income. In this universe, the Afrodescendants represent only 1.7% (IBGE, 2005). Such figures show that the skin color still exerts a predominant influence on the social rising mechanisms. This study aims at the analysis of the Afro-descent issue in the segmentation of Salvador market and, due to that, the question to be discussed here is that of whether the fact of being an Afro-descendant in Brazil determines a behavior of consumption in that group, and which differentiating characteristics of consumption those found in that segment would be. Data concerning the ethnic issue were collected, both as a form of segmentation and as a possible aspect related to the behavior of consumption. The quantitative research was carried out from a probability sample, with 400 consumers- among Afro-descendants and non-Afro-descendants- based on which the consumption habits of Salvador City s Afro-descendant consumers were observed. The preference for certain segments of products among that group was analysed, and the relationship between those preferences and the racial question was verified. Finally, one comes to the conclusion that economic factors - such as income - in the capital of Bahia determine the afrodescendants' and nonafrodescendants' consumption behavior more strongly than the demographic variable race, which is the focus of this study.